Pengaruh Disiplin Kerja dan Pengawasan Kerja Terhadap Efektivitas Kerja Karyawan (Studi Pada PT. Bunga Wangsa Sedjati Kota Batu) - Sri Bulan; Pardiman Pardiman; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2022)
Abstract The purpose of this study was to determine the effect of work discipline and work supervision on employee work effectiveness. The sample in this study was 60 respondents with a population of 60 employees who were in the Back Office of Jawa Timur park 1. In this study, direct random sampling method was used as the sampling method. The questionnaires distributed and then analyzed provided the primary data for this study. IBM's SPSS Statistics Program Version 22 was used for multiple linear regression analysis, the findings of the study of discipline in work and work supervision have a positive effect on employee work efficiency. Keywords: Work Discipline And Supervision Of Employee Work Productivity.